ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.M DI KLINIK UTAMA NILAM SARI TEMBILAHAN TAHUN 2022 - Okta Viarika, Dwi; Erlina Asrita Sari, Dewi (STIKES HUSADA GEMILANG, 2023)
Comprehensive care is a series of continuous and comprehensive activities, from pregnancy, childbirth, postpartum, newborn services, family planning (KB), which aims to provide quality services to prevent MMR and AKB. This care aims to be able to provide midwifery services Comprehensive Care. The midwifery management approach method with a varney mindset is outlined in the form of SOAP. Held at Nilam Sari Main Clinic on March 11 – June 5, 2022. Comprehensive obstetric care was carried out on Mrs.